Complete mitochondrial genomes of three crickets (Orthoptera: Gryllidae) and comparative analyses within Ensifera mitogenomes - Yang, Jing; Ren, Qianli; Huang, Yuan (Zootaxa, 2016)
The complete mitochondrial genomes (mitogenomes) of Velarifictorus hemelytrus, Loxoblemmus equestris and Teleogryllus emma are 16123 bp, 16314 bp and 15697 bp, in size, respectively. All three mitogenomes possess the same gene order of the inversion of the gene cluster trnE-trnS(AGN)-trnN compared with the ancestral gene order of Orthoptera. The atypical initiation codon for the cox1 gene in three crickets is TTA. Pronounced A skew and T skew have been found in Grylloidea comparing with Gryllotalpoidea and Tettigonioidea. The T-stretch in the minority strand is interrupted by C to form (T)n(C)2(T)n sequences in five species of Gryllinae (V. hemelytrus, L. equestris, T. emma, T. oceanicus, T. commodus). This T-stretch variant with its neighbouring A-stretch variant (A-stretch is interrupted by G), which were discovered in the A+T-rich regions of all taxa from infraorder Gryllidea, could form a conserved stem-loop structure (including 15 17 base pairs). This potential stem-loop structure is a favorable candidate that may participate in the replication origin of the minority strand of Gryllidea mitogenome. Phylogenetic analysis indicated that within the Gryllinae, genus Teleogryllus and Velarifictorus are closely related, sister to the genus Loxoblemmus. The relationships among the five superfamilies of Ensifera presented here were ((Grylloidea, Gryllotalpoidea) (Tettigonioidea, (Hagloidea, Rhaphidophoroidea))).